Characterization and optimization of production process of alcoholic fermentation of pineapple - Queiroz, Germana Arruda de; Rabelo, Andryelle Geovana Santos; Santos, Suseanne Kedma de Melo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Fruits are natural sources of vitamins, minerals, carbohydrates and other nutrients. Tropical fruits are consumed and appreciated all over the world due to the taste and flavour. This work aims to evaluate the physicochemical composition of fermented pineapple beverages, study associated fermentation kinetics and optimize fermentation conditions through the use of multiple linear regression and surface response analysis. Pineapple juice was characterized physiochemically using measures of soluble solids (brix), acidity, density and pH. It was determined that a fermentation temperature of 25 °C, pH between 3.0 and 4.0, and inoculum quantity of 4–5 g·L-1 resulted in a high-quality fermented beverage with 8.1% (v/v) ethanol content. A kinetic study was performed on the alcoholic fermentation process, monitoring the following variables: Brix, acidity, density, and alcohol content. The results showed that higher concentrations of yeast results in higher productivity and was possible to optimize the processes to maximize the results. This process is technically viable and can yield a value-added product that can generate revenue as well as other significant economic benefits for the beverage market.